Equity versus bail-in debt in banking: an agency perspective - Caterina Mendicino; Kalin Nikolov; Javier Suarez (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
We examine the optimal size and composition of banks' total loss absorbing capacity (TLAC). Optimal size is driven by the trade-off between providing liquidity services through deposits and minimizing deadweight default costs. Optimal composition (equity vs. bail-in debt) is driven by the relative importance of two incentive problems: risk shifting (mitigated by equity) and private benefit taking (mitigated by debt). Our quantitative results suggest that TLAC size in line with current regulation is appropriate. However, an important fraction of it should consist of bail-in debt because such buffer size makes the costs of risk-shifting relatively less important at the margin.
Keywords: G21; G28; G32; 330; bail-in debt; loss absorbing capacity; risk shifting; agency problems; bank regulation